2014
DOI: 10.1016/j.bbr.2014.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Central injection of relaxin-3 receptor (RXFP3) antagonist peptides reduces motivated food seeking and consumption in C57BL/6J mice

Abstract: Behavioural arousal in mammals is regulated by various interacting central monoamine- and peptide-neurotransmitter/receptor systems, which function to maintain awake, alert and active states required for performance of goal-directed activities essential for survival, including food seeking. Existing anatomical and functional evidence suggests the highly-conserved neuropeptide, relaxin-3, which signals via its cognate Gi/o-protein coupled receptor, RXFP3, contributes to behavioural arousal and feeding behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 83 publications
(142 reference statements)
1
61
1
1
Order By: Relevance
“…Although there is a possibility that the doses of RXFP3-A2 or R3(B1-22)R were not sufficient to elicit a response in all assays, the 1 nmol dose of RXFP3-A2 was similar to that used in our rat study [33] and the 4 nmol dose of R3(B1-22)R was based on a study in mice in which a reduction in several measures of motivated food intake were observed [44], indicating that this is a physiologically active dose. Furthermore, our positive data appear comparable to findings in a study in which a cohort of rats spent an average of ~15% of the total test time in the light half of the L/D box [33], similar to the ~20% of total time spent in the light half by FG-7142/aCSF treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is a possibility that the doses of RXFP3-A2 or R3(B1-22)R were not sufficient to elicit a response in all assays, the 1 nmol dose of RXFP3-A2 was similar to that used in our rat study [33] and the 4 nmol dose of R3(B1-22)R was based on a study in mice in which a reduction in several measures of motivated food intake were observed [44], indicating that this is a physiologically active dose. Furthermore, our positive data appear comparable to findings in a study in which a cohort of rats spent an average of ~15% of the total test time in the light half of the L/D box [33], similar to the ~20% of total time spent in the light half by FG-7142/aCSF treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of innate anxiety in the behavioural tests used previously revealed that icv R3(B1-22)R (4 nmol; a dose shown to reduce motivated food seeking in mice [44]) increased anxiety-like behaviour in the EPM ( Table 2 In regard to the latter, RXFP3 mRNA is abundantly expressed in several brain areas associated with control of anxiety-like behaviours, including the well characterised extended amygdala [6,[50][51][52]. Relaxin-3 is primarily expressed in GABA neurons, as reflected by the co-expression of relaxin-3 and glutamate decarboxylase immunoreactivity in the rat nucleus incertus [18], which suggests RXFP3 activation may act to reinforce inhibitory signalling on target neurons.…”
Section: Effect Of Icv Rxfp3 Antagonist On Basal Anxiety-like Behaviourmentioning
confidence: 97%
See 2 more Smart Citations
“…signaling is implicated in stress and anxiety [41,[48][49][50] , feeding and metabolism [48,[51][52][53] , motivation, reward, and arousal [49,54,55] .…”
Section: Expression Of Relaxin-3 and Rxfp3 In The Brainmentioning
confidence: 99%